Linkage Between Poverty, Inequality, and Income Distribution: A Case on Bannu District, Pakistan - Gul, Akhtar; Zahra, Fatima; Iqbal, Anum; Ghafoor, Tanbila; Hussain, Musaddiq (Asian Development Policy Review, 2020)
Poverty and income inequality are severe problems worldwide, and Pakistan is one of the developing countries that has faced this problem. This study investigates the association between poverty and income inequality in the Bannu district of Khyber Pakhtunkhwa (KPK), Pakistan. Many studies have proven that poverty and income inequality are prevalent in developing countries. In this study, primary data is used for the desired variables, and the simple average, standard deviation, and coefficient of various techniques are used to analyze the data. It was found that poverty is common in this area according to the criteria of the UN and World Bank. Education is also in a poor state, health is at the mercy of God, and unemployment and other socio-economic conditions are widespread. The research shows that there are high levels of poverty and income inequality, as there are in other regions of the state, and this indicates that the government must take steps to eliminate these problems and drive development in the economy.